2010
DOI: 10.1097/paf.0b013e3181fc3568
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death During Prolonged Religious Fasting

Abstract: Sickle cell trait (SCT) is estimated to occur in 6% to 10% of Africans, and the United Kingdom (UK) prevalence rate has been estimated at 3.2%. Although sudden death in sickle cell disease is well known, its occurrence in SCT is rare and requires extremes of physiological stress. We present a case of a 29-year-old black woman who died suddenly during a period of religious fasting. Her medical history was unremarkable, and there was no family history of sickle cell disease. At postmortem, she was found to be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…One report suggested that SCT could be a contributing factor in sudden death occurring during religious fasting (Biedrzycki & Sheaff 2010). Several epidemiological studies and case reports emphasized the possible role of SCT in idiopathic exercise sudden death (Anzalone et al, 2010;Ferster & Eichner, 2012;Harmon et al, 2012;Harris et al, 2012;Hedreville et al, 2009;Kark et al, 1987;Kerle & Nishimura, 1996;Pretzlaff, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One report suggested that SCT could be a contributing factor in sudden death occurring during religious fasting (Biedrzycki & Sheaff 2010). Several epidemiological studies and case reports emphasized the possible role of SCT in idiopathic exercise sudden death (Anzalone et al, 2010;Ferster & Eichner, 2012;Harmon et al, 2012;Harris et al, 2012;Hedreville et al, 2009;Kark et al, 1987;Kerle & Nishimura, 1996;Pretzlaff, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Some recent studies demonstrated that dehydration may cause large hemorheological alterations in SCT carriers (Diaw et al, 2012;Tripette et al, 2010). Indeed, one could hypothesize that impaired blood rheology caused by dehydration during fasting could have been involved in the fatal event described by Biedrzycki and Sheaff (2010). Although several works have focused on the hemorheological changes caused by exercise in SCT carriers (Connes, 2010;Connes et al, 2008aConnes et al, , 2008bTripette et al, 2007Tripette et al, , 2013, no study focused on the hemorheological modifications caused by fasting Ramadan in nonexercising SCT carriers, as well as in the general population.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation